1973
DOI: 10.1007/bf00151803
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric resolution determinations in the fovea and parafovea

Abstract: Foveal and extrafoveal interferometric determinations of retinal resolution were made on two observers. Resolution fell with increasing decentration of fixation.For example, the two subjects exhibited retinal resolution 'equivalent' to Snellen 20/40 respectively at 6.3 ~ and 3.75 ~ from fixation. The test criterion was the ability to distinguish the vertical line (fringe) interferometric pattern formed on the retina. One must conclude that comparable interferometric determinations (resulting in equivalent reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 7 publications
3
30
0
Order By: Relevance
“…The initial contrasts for each staircase were determined by a method of descending limits. A maximum-likelihood procedure, QUEST,1 5 determined the fringe contrast presented on each trial. A single run ended when 25 trials had been presented for each condition.…”
Section: Methodsmentioning
confidence: 99%
“…The initial contrasts for each staircase were determined by a method of descending limits. A maximum-likelihood procedure, QUEST,1 5 determined the fringe contrast presented on each trial. A single run ended when 25 trials had been presented for each condition.…”
Section: Methodsmentioning
confidence: 99%
“…Variables affecting the Stiles-Crawford effect include luminance [11][12][13], wavelength [11,14], and retinal eccentricity [15][16][17]. Choi et al [17] reported that emmetropes have greater directionality than myopes between 10 nasal and 15 temporal retina.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, uncertainties in the values of the refractive indices may affect significantly the calculated results as well as the conclusions reached from the waveguide model [5]. An error estimation of Dn ¼ 1 Â 10 À4 corresponds to an error value of the directionality factor of D ¼ 7 Â 10 À3 mm À2 [7], which is an error of about 5-10% as commonly reported in SCE studies [1,12].…”
Section: The Waveguide Modelmentioning
confidence: 97%